Profitability as a Moderating Effect of Liquidity, Sales Growth and Leverage on Financial Distress in Islamic Commercial Banks - Khofifah Ayu Virnanda; Ulfi Kartika Oktaviana (Institute for Research and Community Empowerment (LPPM TAZKIA), 2022)
Islamic commercial banks are inseparable from the risk of financial distress. Several financial ratios are able to predict Financial Distress. This study aims to determine the effect of Liquidity, Sales Growth, and Leverage on Financial Distress which is moderated by Profitability. The type of data used is panel data so that it uses panel data regression analysis assisted by Eviews 10 software. The moderation variable test uses Moderating Regression Analysis (MRA). Data collection used a purposive sampling method so as to obtain a sample of 13 Islamic commercial banks in the 2014-2020 period. This study uses the Random Effect Model (REM) technique to see the effect of the relationship between liquidity, sales growth, and leverage variables on financial distress variables simultaneously or partially. The results show that the variables of liquidity and leverage have a significant effect on financial distress. While the sales growth variable has no significant effect on financial distress. Variables that can be moderated by profitability are sales growth and leverage, but profitability is unable to moderate the relationship between liquidity and financial distress. Keywords: Islamic commercial banks, Liquidity, Sales Growth, Leverage, Financial Distress